The Wild Turkey: Journey of a Noble Bird - Ron Klataske (Symphony in the Flint Hills, 2009)
For many Kansas residents over forty, we can remember the first time we saw a wild turkey, just as a person's first sighting of a deer was a notable experience in many areas prior to the 1960's. Wild turkeys were abundant residents here prior to and during the early years of European-American settlement, but N. S. Gross reported that they were "nearly extinct" in 1891 when he published the first History of the Birds of Kansas. Turkeys were good table fare, and that led to their demise in the 19th century.
Keywords: wild; birds; Oklahoma; native; natural; extinct; species; conservation; efforts; life; habitat; eating; woodlands; grain; crops; grass; Wild Turkey